Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
[tex]\frac{x^{2}-6x-16}{x+2}=\frac{x^{2}-6x-2x+2x-16}{x+2}=\frac{x^{2}-8x +2x-16}{x+2}=\\ \\ = \frac {( x -8 ) +2(x-8)}{x+2}=\frac {( x -8 )(x +2)}{x+2}=x-8[/tex]
In algebra, the polynomial remainder theorem or little Bézout's theorem is an application of Euclidean division of polynomials. It states that the remainder of the division of a polynomial by a linear polynomial is equal to In particular, is a divisor of if and only if
a = -2;
f(-2) = (-2)^2 -6*(-2) -16 = 4 + 12 - 16 = 0 => x-(-2) is a divisor of x^2-6x-16.
a = -2;
f(-2) = (-2)^2 -6*(-2) -16 = 4 + 12 - 16 = 0 => x-(-2) is a divisor of x^2-6x-16.
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.